THE SEMIOTICS OF BATAK TOBA SOCIETY MARRIAGE TRADITION - Pininta Veronika Silalahi (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2019)
Marriage is one of the culture universals being that it is contracted in every society of the world, but its mode of contract varies from one society to the other. Marriage is one of life’s major passages, one of the most profound rites of passage that a person or a couple can experience. In many cultures, marriage is generally made known to the public through marriage ceremony. This paper unravels the semiotics of a marriage tradition in Batak Toba Society. Batak Toba is one of the ethnic groups of Batak society, which is still doing wedding tradition as one of its cultural activities. The theoretical framework applied is the conception of signs by Charles Sanders Peirce. According to Peirce, ‘meaning’ is a triadic relation between a sign, an object, and an interpretant. There are three types of signs: icon, index and symbol. This work will reveal the meaning of icons, indexes and symbols in the marriage tradition.